Ocular brachytherapy dosimetry for [Formula: see text] and [Formula: see text] in the presence of gold nanoparticles: a Monte Carlo study - Asadi, Somayeh (J Appl Clin Med Phys, 2016)
The aim of the present Monte Carlo study is to evaluate the variation of energy deposition in healthy tissues in the human eye which is irradiated by brachytherapy sources in comparison with the resultant dose increase in the gold nanoparticle (GNP)‐loaded choroidal melanoma. The effects of these nanoparticles on normal tissues are compared between [Formula: see text] and [Formula: see text] as two ophthalmic brachytherapy sources. Dose distribution in the tumor and healthy tissues has been taken into account for both brachytherapy sources. Also, in certain points of the eye, the ratio of the absorbed dose by the normal tissue in the presence of GNPs to the absorbed dose by the same point in the absence of GNPs has been calculated. In addition, differences of the absorbed dose in the tumor observed in the comparison of simple water phantom and actual simulated human eye in presence of GNPs are also a matter of interest that have been considered in the present work. The difference between the eye globe and the water phantom is more obvious for [Formula: see text] than that of the [Formula: see text] when the ophthalmic dosimetry is done in the presence of GNPs. Whenever these nanoparticles are utilized in enhancing the absorbed dose by the tumor, the use of [Formula: see text] brachytherapy source will greatly amplify the amount of dose enhancement factor (DEF) in the tumor site without inflicting much damage to healthy organs, when compared to the [Formula: see text] source. For instance, in the concentration of 30 mg GNPs, the difference amongst the calculated DEF for [Formula: see text] between these phantoms is 5.3%, while it is 2.45% for [Formula: see text]. Furthermore, in Monte Carlo studies of eye brachytherapy, more precise definition of the eye phantom instead of a water phantom will become increasingly important when we use [Formula: see text] as opposed to [Formula: see text]. PACS number(s): 87.53.Jw, 87.85.Rs, 87.10.Rt